Aksiologi Talak Dan Rekonsiliasi Dalam Kasus Perselingkuhan Digital Pada Pasangan Muda Muslim - Zahratunnisa; Aisyah Putri Salsabila; M. Aunul Hakim (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2025)
Digital infidelity among young Muslim couples has increased alongside the expansion of media ecologies that reshape interpersonal intimacy, trust structures, and hybrid interaction spaces. This study examines how virtual cheating contributes to marital conflict and divorce, and reassesses the axiology of ṭalāq within Islamic legal philosophy to determine the moral value, intentionality, and ethical limits of divorce in the digital era. Using a qualitative library-based method with a normative–philosophical approach, this research employs interpretive and conceptual analysis of literature on digital infidelity, the axiology of divorce, and maqāṣid al-sharī‘ah. The findings reveal that digital cheating generates ambiguous evidence, multilayered trust erosion, and violations of intentionality that are morally comparable to physical infidelity. The axiological analysis affirms that the legitimacy of ṭalāq in digital cases depends on the degree of harm, emotional betrayal, and the feasibility of reconciliation. This study offers an ethical framework for assessing divorce and a value-based reconciliation model grounded in Islamic philosophy, contributing conceptually to contemporary Islamic family law in the context of digital relational transformation.